Technology and Realization of Sectional-spaced Ground Power Supply for Tram - Hongguang GAO; Zhongde GAO; Xueli LI; Lin CHEN; Jianzhong JI; Guangtai CHEN; Tao CHEN (机车电传动)
According to the present situation of the tram ground power supply technology at domestic and abroad, the sectional-spaced ground power supply system scheme and realization method were put forward. The system control method was illustrated through judging from the ground state of power supply and vehicle-mounted uninterruptible power supply to charge and discharge control strategy. With the system simulation and experimental research of the operation energy and technology application on the Zhuhai tram line 1, the technical and economic advantages of the sectional-spaced ground power supply system was analyzed.